2021
DOI: 10.1177/13591053211037727
|View full text |Cite
|
Sign up to set email alerts
|

The long arm of childhood: The prolonged influence of adverse childhood experiences on depression during middle and old age in China

Abstract: Utilizing data from the nationally representative China Health and Retirement Longitudinal Study, this study analyzed the effect of intensity and duration of adverse childhood experiences on depression in middle aged and older aged adults in China. The mediating effect of cumulative health risk and personal factors were validated through the Karlson–Holm–Breen method. The results showed a significant dose-response relationship between adverse childhood experiences and adult depression. The elevated health risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Our study has also extended the literature on the association between ACEs and subsequent risk of increasing depressive symptoms (e.g., [ 5 ]) and suicidal behavior (e.g., [ 46 ]). In addition to the prolonged adverse impact of ACEs during childhood on future adults’ mental health demonstrated in previous studies (e.g., [ 47 ]), adversities during childhood also showed immediate impact on children’s mental health. Furthermore, although verbal abuse and emotional neglect were more commonly labeled as a normal parenting practice in rural China, compared with physical and sexual abuse being treated as evident trauma, our study highlighted that these types of obscure or less evident childhood trauma demonstrated a severe impact on children’s mental health.…”
Section: Discussionmentioning
confidence: 76%
“…Our study has also extended the literature on the association between ACEs and subsequent risk of increasing depressive symptoms (e.g., [ 5 ]) and suicidal behavior (e.g., [ 46 ]). In addition to the prolonged adverse impact of ACEs during childhood on future adults’ mental health demonstrated in previous studies (e.g., [ 47 ]), adversities during childhood also showed immediate impact on children’s mental health. Furthermore, although verbal abuse and emotional neglect were more commonly labeled as a normal parenting practice in rural China, compared with physical and sexual abuse being treated as evident trauma, our study highlighted that these types of obscure or less evident childhood trauma demonstrated a severe impact on children’s mental health.…”
Section: Discussionmentioning
confidence: 76%
“…The original ACE study demonstrated a strong dose-response relationship between ACE score and the probability of lifetime and recent depressive disorders [46]. Longitudinal results from China also demonstrate a significant dose-response relationship between ACEs and adult depression [47]. There is a paucity of literature documenting doseresponse associations between ACEs and anxiety, and none of the studies have been specific to MSM.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the current study demonstrated that not all ACEs cause depression in adulthood and further illustrated that different ACEs have different outcomes. Although the ever-increasing literature indicates that ACEs may trigger mental health problems, such as depression [ 2 , 4 ], not all individuals who experience ACEs develop depression. Five ACEs (parental divorce, parental death, parental drug abuse, parental alcoholism, and parental crime) did not cause depression in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial empirical evidence from multiple countries has demonstrated that adverse childhood experiences (ACEs) are highly correlated with depression in adulthood [ 1 , 2 , 3 ]. For example, scholars have long believed that ACEs may enhance vulnerability to psychological development throughout the course of a person’s life, specifically depression [ 4 , 5 , 6 , 7 , 8 ]. In addition, some meta-analyses confirm that a history of ACEs significantly increases the risk of depression and anxiety in adulthood [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%